Geoturismo en el cantón Penipe, provincia de Chimborazo como parte del proyecto Geoparque Volcán Tungurahua - Guamán Lliquin, Wendy Mariuxi (2024)
ABSTRACT: Geotourism is a new type of tourism that focuses on the importance of geology, local economic development, and conserving geosites. The purpose of this report is to examine geotourism with the goal of improving both the Geopark and the Canton. Key aspects were considered like geological heritage, interpretation, and conservation. The study used descriptive, documentary, and observational research methods. A descriptive approach, along with documentary and observational research, were used, with a cross-sectional, non-experimental design that integrated qualitative and quantitative methodologies. The data collection instruments used for this research included surveys, interviews, and observation sheets. Specifically, surveys were applied to tourists visiting the Penipe canton, field research was conducted using observation sheets in the four geosites of the canton, and interviews were conducted with two members of the Tungurahua Volcano Geopark, which is an area that aspires to UNESCO recognition. Based on the results of the survey, both national and international tourists see Penipe Canton as a great destination because of its geological structures. However, many are unaware of geotourism or the Tungurahua Volcano Geopark. Finally, a proposal was made to create a virtual information guide about geotourism and Penipe Canton's geosites titled "PENIPE, Explore its breathtaking geological treasures." This guide includes details about Geopark Volcán Tungurahua, educational content about activities at each geosite, geological features, visitor tips, and more, all written in an easy-to-understand language.